The university library as a complex adaptive system (CAS) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
The paper introduces a theoretical model based on literature review for understanding the University Libraries as Complex Adaptive Systems, introducing a new methodology to deal with these institutions. It is a possibility for University Libraries managers to glimpse the unstable scenario of these institutions. This approach is based on the literature review to identify approaches considering the complexity within the libraries in order to base the construction of a model as a proposal. Although there are approaches that consider the University Library as a complex institution, it attests that this is not considered in its entirety, that is, not all its services and agents are involved, but only focus on some aspects or services. Besides, the characterization and understanding of the University Library as a Complex Adaptive System is unknown in the literature. The proposal of a model facilitates the understanding and provides the possibility of practical application for characterization of these institutions, University Libraries, as Complex Adaptive Systems, providing different types of knowledge, as well as the strategies and actions necessary to adapt to the ephemeral context in which they operate.Keywords: University Libraries. Information Science. Knowledge Management. Complexity. Complex Adaptive System.Link: http://www2.marilia.unesp.br/revistas/index.php/bjis/article/view/5546/4510